Use of pullulanase as a biocatalyst for starch hydrolysis: Part 1. Study of the effect of pullulanase on maize amylopectin starch - A. A. Papakhin; Z. M. Borodina (Пищевые системы, 2022)
The use of debranching enzymes in starch hydrolysis is a topical direction for obtaining new types of starch products with controlled properties and a potential for the further use. The aim of the work was to study an effect of pullulanase (EC3.2.1.41) on maize amylopectin starch in the native and gelatinized state. The objects of the research were maize amylopectin starch and enzyme preparation Promozyme D6 (Novozymes, Denmark). High-performance liquid chromatography (HPLC) was used to determine the carbohydrate composition of hydrolysates. The mass fraction of reducing substances (RS) was determined by the Lane and Eynon method. A rotational viscometer was used to measure dynamic viscosity of the starch hydrolysis products. It was found that analyzed starch in the native state showed low enzymatic sensitivity to the action of pullulanase with insignificant changes in viscosity, solubility and iodine binding capacity of the samples. Pullulanase showed the highest effect on gelatinized starch during the first eight hours of incubation. After eight hours, the maximum degree of starch hydrolysis by pullulanase at a dose of 10 units/g dry matter (DM) was 4.7% on DM basis, iodine binding capacity of the hydrolysate was D600 = 0.343 (in the control experiment D600 = 0.154), and the viscosity of the hydrolysate decreased from 7887 mPa · s to 4.3 mPa · s. Hydrolysates cooled to 8 °C and held for 20 hours along with hydrolysates that were not cooled showed high susceptibility to attack by glucoamilase (97–98%) at 60 °C and 24 hours of saccharification, which suggested the absence of their resistance to the action of glucoamilase in the conditions of the experiment. The use of pullulanase in dextrinization of the analyzed starch, which was gelatinized and partly hydrolyzed by α-amylase (RS6.1%), enabled obtaining hydrolysates with the mass fraction of reducing substances in a range of 10–24% on DM basis with the process duration of 2 to 24 hours and the enzyme dose of 2–10 units, which contained mainly maltotriose, maltohexose and maltoheptose with their total amount of 45–60% on DM basis. The results indicate a need for further research of the biocatalytic action of pullulanase to develop new methods for enzymatic modification of starch.